ICT and the Foresight Infrastructure of the Future: Effects on the Foresight Discipline - Keller, Jonas; von der Gracht, Heiko (World Future Review, 2014)
Information and communication technology (ICT) is being increasingly set up to improve the infrastructure of foresight. It will likely be used to implement more routine and continuous foresight processes in companies and organizations in the future. In this research, we look at the future implications of growing ICT application in foresight based on an extensive worldwide Delphi survey.